Management of Crocodiles (Crocodylus acutus) in Tilapia Farming Ponds in Cañas, Guanacaste - Bolaños, Juan Rafael (2012)
I tackled the problem of implementing the control of crocodiles (Crocodylus acutus) in tilapia (Oreochromis niloticus) acuaculture ponds. It was necessary to reduce the fish consumption by crocs, as well as to potentiate workers safety. The project evolved during a six years time span from the by hand capture and releasing in a far away spot of the Tempisque river, to the design of a managent plan for a generalized control of crocodiles in the whole Tempisque´s Great Wetland, based on the results of a formal research which stated the status of the TGW´s crocodile population.